On the ideological front : the Russian intelligentsia and the making of the Soviet public sphere - Finkel, Stuart, 1970- (Yale University Press, 2007)
'On the Ideological Front' centres on the 1922-23 expulsion from Soviet Russia of some 100 prominent intellectuals. Finkel's account is a scholarly examination of this which sets it in the context of Bolshevik curbs, prohibitions, and punishment of intellectuals who resisted ideological conformity.